2009
DOI: 10.1111/j.1751-553x.2008.01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of red cells, nucleic acid‐containing cells and platelets (RNP Determination) by a crossover analysis of emission DNA/RNA light

Abstract: We developed a new flow cytometry analysis method using a crossover analysis of emission light from intracellular DNA/RNA. Both the RNA and the DNA content in each cell were new parameters obtained by fluorescence analysis using acridine orange supravital stain. With this method, two-dimensional diagrams produced by cellular RNA concentration (CRc) and cellular DNA concentration (CDc) enabled clear separation of red cells and platelets, and the diagram (RNP Diagram) also distinguished fluorescently stained blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…We used blue light (488 nm) for fluorescence excitation and measure cell fluorescence in green (F530, 530/20 nm) and red (F695, 695/40 nm) light wavelength. Previously it was reported that the amount of DNA was determined by green fluorescence, and the amount of RNA by red fluorescence, and the cellular RNA concentration (CRc) and cellular DNA concentration (CDc) values could be evaluated by calculating the ratio between the RNA and FSC or DNA and FSC characteristics of each event, respectively 21 . Based on this report of, we defined the cellular red and green fluorescence intensity as red fluorescence intensity per FSC (F695/FSC) and green fluorescence intensity per FSC (F530/FSC), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used blue light (488 nm) for fluorescence excitation and measure cell fluorescence in green (F530, 530/20 nm) and red (F695, 695/40 nm) light wavelength. Previously it was reported that the amount of DNA was determined by green fluorescence, and the amount of RNA by red fluorescence, and the cellular RNA concentration (CRc) and cellular DNA concentration (CDc) values could be evaluated by calculating the ratio between the RNA and FSC or DNA and FSC characteristics of each event, respectively 21 . Based on this report of, we defined the cellular red and green fluorescence intensity as red fluorescence intensity per FSC (F695/FSC) and green fluorescence intensity per FSC (F530/FSC), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This type of staining enables clinicians to diagnose patients with chronic lymphocytic leukaemia, pertussis, hypogammaglobulinemia, acute leukaemia, uraemia, and other malignancies, as well as to distinguish human reticulocytes from erythrocytes. Moreover, morphological abnormalities present in human erythrocytes, such as red blood cell fragments and large platelets can be detected via FCM with AO staining 21 . In this study, six parameters were used to identify blood cell types: forward-scattered light (FSC), side-scattered light (SSC), nucleic acid and intracellular granule information obtained from green (F530) and red (F695) fluorescence intensity, cellular red fluorescence intensity (F695/FSC), and cellular green fluorescence intensity (F530/FSC).…”
Section: Introductionmentioning
confidence: 99%
“…The prototype Celltac G+™ HA uses a novel reticulocyte identification method that involves metachromatic nucleic acid staining with acridine orange (AO) and is based on a crossover analysis of the light emitted by DNA and RNA 3 (determination of red cells, nucleic acid‐containing cells, and platelets; RNP Determination™). The red and green fluorescence generated by staining of single‐stranded RNA and double‐stranded DNA reflects immaturity and morphological abnormality of erythrocytes by detecting their RNA and DNA content.…”
Section: Introductionmentioning
confidence: 99%